2021
DOI: 10.1186/s13023-021-02013-x
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of rare and monogenic diseases in pediatric organ transplant recipients in Italy

Abstract: Background Rare diseases are chronic and life-threatening disorders affecting < 1 person every 2,000. For most of them, clinical symptoms and signs can be observed at birth or childhood. Approximately 80% of all rare diseases have a genetic background and most of them are monogenic conditions. In addition, while the majority of these diseases is still incurable, early diagnosis and specific treatment can improve patients’ quality of life. Transplantation is among the therapeutic options and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 44 publications
(35 reference statements)
0
8
0
2
Order By: Relevance
“…The most recent analyses on adult and pediatric patients, who have received a kidney transplant or are included in the transplant waiting list or are present in the registries of the European Renal Association-European Dialysis and Transplant Association (ERA-EDTA) indicate that up to 27% of them are undiagnosed at the time of transplantation [ 7 ]. In line with these data, by analyzing the Transplant Registry of the Italian National Transplant Center, we recently reported that approximately 17.2% of the pediatric cohort was without a clear clinical diagnosis [ 6 ]. In addition, when considering the different disease categories, the great majority was affected by rare conditions and up to 50% by a monogenic disease [ 6 ].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The most recent analyses on adult and pediatric patients, who have received a kidney transplant or are included in the transplant waiting list or are present in the registries of the European Renal Association-European Dialysis and Transplant Association (ERA-EDTA) indicate that up to 27% of them are undiagnosed at the time of transplantation [ 7 ]. In line with these data, by analyzing the Transplant Registry of the Italian National Transplant Center, we recently reported that approximately 17.2% of the pediatric cohort was without a clear clinical diagnosis [ 6 ]. In addition, when considering the different disease categories, the great majority was affected by rare conditions and up to 50% by a monogenic disease [ 6 ].…”
Section: Discussionmentioning
confidence: 93%
“…In line with these data, by analyzing the Transplant Registry of the Italian National Transplant Center, we recently reported that approximately 17.2% of the pediatric cohort was without a clear clinical diagnosis [ 6 ]. In addition, when considering the different disease categories, the great majority was affected by rare conditions and up to 50% by a monogenic disease [ 6 ]. These results suggest that genetic screening may be a valuable addition for increasing the diagnostic rate.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…), распространенность 1 пациент на 10 000 человек населения является достаточным показателем для РЗ [21]. Кроме того, некоторым РЗ присуща определенная эндемичность и специфич ность для конкретной популяции, несмотря на их редкую встречаемость [4].…”
Section: распространенностьunclassified
“…Довольно часто эти заболевания носят семейный характер. Безусловно, медико-генетические и ла бораторно-генетические методы исследования и, в частности, новые технологии секвенирования ДНК и РНК расширили границы понимания мно гих редких и малоизученных заболеваний, а также помогли в установлении ранее не известных и не описанных нозологических форм [4]. Нередко они ассоциированы с тяжелой клинической картиной.…”
unclassified